Gastronomic Experience as a Factor of Motivation and Satisfaction in Coastal Destinations - VILLAGÓMEZ-BUELE, César; CARVACHE-FRANCO, Mauricio; CARVACHE-FRANCO, Orly; CARVACHE-FRANCO, Wilmer; VILLAVICENCIO-PÁRRAGA, Mirian (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
Gastronomy is an immaterial resource that, in coastal destinations, offers a great variety of seafood dishes to attract visitors. The purpose of this study was to analyze tourists’ gastronomic experience as a factor of motivation and satisfaction in coastal destinations . This research was carried out in Esmeraldas province in Ecuador. 385 valid questionnaires were statistically analyzed using multiple correlation and regression techniques. The results show that the gastronomic motivations that most influenced tourists’ satisfaction were “enjoying seafood,” “trying a typical dish,” and “enjoy eating on the beach.” Concerning service aspects, visitors were most satisfied with the taste and quality of the food, the variety of dishes, and the service and employee courtesy. These findings will contribute as guides for managers of tourist destinations with gastronomic potential and for tourist companies to develop products according to the demand.